In silico identification of SARS-CoV-2 spike (S) protein–ACE2 complex inhibitors from eight Tecoma species and cultivars analyzed by LC-MS. Issue 70 (26th November 2020) - El Hawary, Seham S.; Khattab, Amira R.; Marzouk, Hanan S.; El Senousy, Amira S.; Alex, Mariam G. A.; Aly, Omar M.; Teleb, Mohamed; Abdelmohsen, Usama Ramadan
Abstract : In silico exploration of 12 Tecoma phytocompounds that could serve as potential inhibitors of SARS-CoV entry to host cells. Abstract : Coronavirus (CoV) is a positive RNA genome virus causing a global panic nowadays. Tecoma is a medicinally-valuable genus in the Bignoniaceae family, with some of its species exhibiting anti-HIV activity. This encouraged us to conduct an in silico exploration of some phytocompounds in Tecoma species cultivated in Egypt, namely Tecoma capensis and its four varieties i.e. yellow, harmony, pink and red, T. grandiflora Loisel., T. radicans L., and one hybrid i.e. Tecoma × smithii W. Watson. LC/MS-based metabolite profiling of the studied Tecoma plants resulted in the dereplication of 12 compounds (1–12 ) belonging to different phytochemical classes viz. alkaloids, iridoids, flavonoids and fatty acid esters. The in silico inhibitory action of these compounds against SARS-CoV-2 spike protein C-terminal domain in complex with human ACE2 was assessed via molecular docking. Succinic acid decyl-3-oxobut-2-yl ester (10 ), a fatty acid ester, possessed the best binding affinity (−6.77 kcal mol −1 ), as compared to hesperidin (13 ) (−7.10 kcal mol −1 ).